Communication studies and their integration: experience of NORDICOM - Gudonienė, Vilija (Information & Media, 1994)
Communication studies in Vilnius University started in 1991. The main problems concerning media studies curriculum development and research are rooted in a highly multidisciplinary character of the field, disintegration of both - the research and academic institutions. The experience of NORDICOM (Nordic Documentation Center for Mass Communication Research) in documentation and spreading information about academic research in the field of media and communication among the members of research community, users of research and international research organizations is presented as the pattern to follow in Lithuania
Keywords: -